2009
DOI: 10.1590/s0103-90162009000400012
|View full text |Cite
|
Sign up to set email alerts
|

EDTA assisted phytorremediation of a Pb contamined soil: metal leaching and uptake by jack beans

Abstract: Lead (Pb) is one of the main soil contaminants. It is also of difficult phytoremediation due to its low solubility and high retention on soil particles. EDTA application to soil is a strategy to increase heavy metal phytoextraction, but such chelants usually cause phytotoxicity and metal leaching side effects. Therefore, these research work objectives were to evaluate the effects of single (0.5 g kg -1 ) and split (0.25 + 0.25 g kg -1 ) EDTA application on Pb uptake by jack beans (Canavalia ensiformis L.) as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 28 publications
(23 reference statements)
2
13
0
6
Order By: Relevance
“…This positive findings disagree with Geebelen et al (2002) and Wang et al (2007) who found reduction in shoot length and weight of bean (Phaseolus vulgaris L.) and Bibens maximowicziana L. after increasing Pb rates and EDTA addition. Results of this study indicate a good potential of the jack bean as a Pb phytoextractor plant due to its high dry matter yield on tropical soils, which was confirmed by Gabos et al (2009). On the other hand, for treatments without EDTA, shoot dry matter yields decreased with increasing Pb rates and presented the lowest yield at the highest Pb rate (2,400 mg kg -1 ).…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…This positive findings disagree with Geebelen et al (2002) and Wang et al (2007) who found reduction in shoot length and weight of bean (Phaseolus vulgaris L.) and Bibens maximowicziana L. after increasing Pb rates and EDTA addition. Results of this study indicate a good potential of the jack bean as a Pb phytoextractor plant due to its high dry matter yield on tropical soils, which was confirmed by Gabos et al (2009). On the other hand, for treatments without EDTA, shoot dry matter yields decreased with increasing Pb rates and presented the lowest yield at the highest Pb rate (2,400 mg kg -1 ).…”
Section: Resultssupporting
confidence: 69%
“…However, although the biomass production of tropical species is generally high, only few studies have been carried out with the objective to identify tropical species with good phytoextraction potential. In addition few studies have been carried out with tropical soils and phytoextraction (Gabos et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is related to the binding between organic compounds of vinasse and Pb in the soil solution, which enhanced mobility through the soil columns, under the successive leaching. Similar results were found for soil columns under the influence of EDTA in an Oxisol (Gabos et al, 2009), and citrate and oxalate in a Spodosol (Freitas et al, 2009) columns (the same size used in this work) was enhanced when soils were treated with two wastewaters from an agricultural industry (olive-mill wastewater and concentrated sugarbeet vinasse) (Madrid and Díaz-Barrientos, 1998).…”
Section: Pb Leaching Experimentssupporting
confidence: 83%
“…Among the few studies available in Brazil, many have been restricted to academics (Carneiro et al, 2001;Coscione and Berton, 2009;Gabos et al, 2009;Marques et al, 2000;Pereira et al, 2007;Romeiro et al, 2006;Santos et al, 2007;Zeittouni et al, 2007). In spite of that, promising species well known in Brazilian agriculture due to its robustness, good climate adaptation, deep root system and good biomass production have not been evaluated.…”
Section: Introductionmentioning
confidence: 99%